Food Loss and Waste In North Sumatra, Indonesia: Policy Recomendations - Mutiara Fahmi (Universitas Teuku Umar, 2024)
The issue of food loss and waste (FLW) In North Sumatra, Indonesia brings significant threats that ultimately affect social, economic, and environmental conditions. The inefficiencies in food production, distribution, and consumption worsen the region's food insecurity, financial losses, and environmental degradation. This study examines the primary reasons and effects of FLW in North Sumatra, including cultural habits, inadequate waste management systems, and infrastructural shortcomings. The paper offers actionable recommendations based on thoroughly evaluating national regulations, local initiatives, and international best practices. Suggestions include investing in advanced processing and storage technologies, enhancing food recovery systems, adopting circular economy principles, and promoting public awareness campaigns. By addressing these challenges through collaborative efforts among stakeholders and innovative policy strategies, North Sumatra can significantly reduce FLW, improve food security, and contribute to Indonesia's broader sustainability goals—especially its commitment to UN Sustainable Development Goal 12.3. This study underscores the importance of integrating social, environmental, and economic considerations into strategies for mitigating FLW to ensure long-term regional development.